(untitled) (REMUNOM, 2025)
One of the challenges teachers have faced is aligning the theoretical content of mathematics with teaching strategies that engage students’ interest. This work originated from observing gaps in the mathematics learning of students in the final years of elementary school in the municipality of Oeiras - PI. In this context, we investigate the following research problem: What are the contributions of using golden material in the restructuring of mathematics learning from the perspective of 6th grade students at the Municipal School of Contentamento, Oeiras-PI? With the general objective: To analyze the perception of 6th-grade students from a public school regarding the contributions of using golden material in understanding and solving fundamental operations and specific objectives: identify the difficulties of students in fundamental operations; identify the challenges that students encountered while using the golden material; list the discoveries made by students while manipulating the golden material and describe the contribution of the golden material to the development of strategies for problem-solving. The methodology adopted was action research as a way to intervene in the students’ reality, with a quantitative and qualitative approach, applying data collection instruments such as: pre-test, intervention workshops, and post-test. We also used semi-structured interviews and observation of records in a logbook as support in the investigation. The results indicated that the use of the golden material significantly contributed to the evolution of students’ learning in the four fundamental operations, as well as in working with decimal numbers.